HUBUNGAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENGETAHUAN PESERTA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DENGAN ALUR PROSEDUR PELAYANAN PASIEN RAWAT JALAN - Simarmata, Marice (Jurnal Penelitian Kesmasy, 2021)
The flow of service procedures is the Rules or systems there are made to serve or meet the needs of others to get care about health without the need for lodging. Health services had a plot and procedures that must be known and obeyed by BPJS patients. The completeness of administrative requirements will affect the rapid or delayed process of health services. The purpose of this study is to determine the relationship of Factors Affecting the Knowledge of Participants Social Security Agency (BPJS with the Procedure of patient services In Grandmed Hospital Lubuk Pakam 2017. This research is an analytic research. This type of research used an observational design with Cross sectional approach. The population in this study were all outpatients using BPJS health at Grandmed Hospital Lubuk Pakam Hospital were the outpatient BPJS hospital patients at Grandmed Hospital lubuk pakam. The Sample in this research was partial of BPJS patient of outpatient of 30 people. Sampling in this research was done by using technique of non probability sampling, that was Quota sampling. There are no age correlation with service procedure flow with value (p) = 0,696> 0,05. There are an information relation with service procedure flow with value (p) = 0,018 <0,05. There are an educational relationship with the service procedure flow with the value (p) = 0.005 <0.05. There are no work relationship with the service procedure flow with the value (p) = 0.385> 0.05. It are expected that the health BPJS participants should be more active in finding information about the service procedure flow applied by the hospital Grandmed hospital so that the BPJS health participants who will conduct outpatient treatment to made the registration process faster.